Leukemia Stem Cell Frequency at Diagnosis Correlates With Measurable/Minimal Residual Disease and Impacts Survival in Adult Acute Myeloid Leukemia - Kamel, Azza M.; Elsharkawy, Nahla M.; Kandeel, Eman Z.; Hanafi, Marwa; Samra, Mohammed; Osman, Randa A. (Frontiers in Oncology, 2022)
Acute myeloid leukemia is a heterogenous disease in which the initiation and maintenance of the malignant clone is blamed on a rare population of leukemia stem cells (LSC). The persistence of such a malignant population is referred to as measurable/minimal/residual disease (MRD). Evaluation of MRD is the gold standard for follow up of therapy and constitutes an independent prognostic parameter. As LSCs is the main contributor to persistence of MRD, then it should correlate to the bulk of LSCs at the individual case level. MRD is measured at defined time points during therapy. However, LSCs can be evaluated at diagnosis which gives it the advantage of early prediction of high-risk patients and allow early proper therapeutic decisions. Using two simple 4 color monoclonal antibody combinations (CD38/CD123/CD34/CD45 and CD90/CD133/CD45/CD33) and the prism function of Coulter Naviose flow cytometer, the frequency of LSC subsets was evaluated in 84 newly diagnosed adult AML patients. For each panel, 16 possible combinations were detected. Our results showed that there is extreme variability in % of LSC fraction between different cases, as well as at the individual case level. For each LSC subset, the median value was used to divide cases into low and high expressors. LSC subsets that showed an impact on OS and DFS included: CD123+, CD 123+/CD34-, CD34-/CD38+/CD123+, CD34+/CD38-/CD123+, CD133+, CD133+/CD33-. On multivariate analysis only CD123 (P=˂0.001, SE=0.266, HR=2.8, 95% CI =1.74.7). and CD133+/CD33- (P = 0.017, SE= 0.263, HR =1.9, 95% CI=1.1- 3.1) retained their significance for OS. Likewise, only CD34+/CD38-/CD123+ (p=<0.001, HR 2.3, SE: 0.499, 95% CI: 2.4-17.4) and CD133 (p= 0.015, HR 2.3, SE 0.34, 95% CI: 1.2- 4.4) retained statistical significance for DFS. LSC frequency at diagnosis showed moderate to strong correlation with MRD status at day 14 and day 28. In conclusion the level of LSC in AML cases at diagnosis correlates with MRD status at day 14 and day 28 in AML patients and has a deleterious impact on OS and DFS. It may be used as an early marker for high-risk patients allowing for proper early therapeutic decisions.